Analysis of Brand Equity Dimensions, Relationship Marketing, Brand Equity on Panin Bonanza Program - Rina Purnama; Ari Giantika Chandara; Ropidin Ropidin (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
This study aims to determine the effect of brand equity dimensions on brand equity, to determine brand equity dimensions on relationship marketing, and to determine the effect of relationship marketing on brand equity in the formation of Panin Bonanza Brand Equity at PT Bank Panin KCU Senayan. The data analysis technique used is the Structural Equational Modeling (SEM) method, the method of collecting data using a questionnaire to the customers of PT Bank Panin KCU Senayan who participated in the Panin Bonanza Program. Sampling technique using purposive sampling method with a sample size of 110 respondents. Based on the results of the study it can be concluded that the Equty Brand Dimension, Relationship Marketing has a positive influence on Brand Equity, the Brand Equity Dimension also has a positive influence on Relationship Marketing.